2010
DOI: 10.1021/ie1001586
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Lactic Acid by Alkaline Hydrothermal Conversion of Glycerol at High Glycerol Concentration

Abstract: The synthesis of lactic acid by alkaline hydrothermal conversion of glycerol at high glycerol concentrations under autogenous pressure is described. Temperature (250−290 °C), NaOH/glycerol molar ratio (1.1−1.75), glycerol concentration (2.5−3.5 M), and reaction time (30−250 min) have been the variables studied with temperature and NaOH/glycerol molar ratio having the major influence. An 84.5% lactic acid (as sodium lactate) yield is obtained at 280 °C and 90 min with a 2.5 M glycerol concentration and a 1.1 Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
109
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 17 publications
5
109
0
1
Order By: Relevance
“…High NaOH concentration probably caused the decomposition of resultant products to carbonate. 12 The results revealed that high NaOH/glycerol mole ratio favored the hydrothermal conversion of glycerol. But excessive NaOH decreased the selectivity of lactic acid.…”
Section: 19mentioning
confidence: 82%
See 2 more Smart Citations
“…High NaOH concentration probably caused the decomposition of resultant products to carbonate. 12 The results revealed that high NaOH/glycerol mole ratio favored the hydrothermal conversion of glycerol. But excessive NaOH decreased the selectivity of lactic acid.…”
Section: 19mentioning
confidence: 82%
“…The presence of CuAu x catalysts decreased the reaction temperature by 80 C as compared to the hydrothermal method. 11,12 The CuAu x catalysts gave higher lactic acid yield at a higher glycerol concentration than the noble metal catalysts.…”
Section: 19mentioning
confidence: 99%
See 1 more Smart Citation
“…Higher glycerol concentrations were applied by Lopez et al, which resulted in 84% lactic acid yield in 1.5 h at 553 K [29]. KOH has superior activity compared to NaOH in the reaction [30].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported high yields of lactic acid (> 90%) from many carbon sources (glycerol, sorbitol, mannitol) (Kishida et al, 2005;Ramírez-López et al, 2010;Shen et al, 2009;Zhou et al, 2010). These studies, however, started from low concentrations of the carbon source (< 0.05 v/v).…”
Section: Introductionmentioning
confidence: 99%